แนวทางการใช้กฎหมายเพื่อปกป้องภาวะโลกร้อน ภายในคณะนิติศาสตร์ มหาวิทยาลัยราชภัฏรำไพพรรณี - อิทธิมีชัย ฐิติรัตน์; ประมาณ ทรงพร; โภคสุทธิ์ อาทิตยา (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2019)
The objectives of this research were 1. to study the impact and importance of global warming, 2. to study the guidelines for using law within the Faculty of Law, and 3. to suggest the legal measures to protect the world from global warming by using mixed method research between quantitative and qualitative research. The researcher assigned a sample group of 112 students from the Faculty of Law, who used the service of the school building. Research tools used was a questionnaire related to law enforcement measures to cover global conditions within the Faculty of Law and analyzed data by using Likert statistics. As for qualitative research, it was the study of document research. The results of the study showed as follows: 1. The effects of global warming did not create a serious impact on life or affect the life in learning and living in the Faculty of Law students. In this section, the assessment results were at the moderate level (x = 2.63). However, global warming is still a national problem that needs to be handled and accelerated to find measures to reduce global warming in all dimensions. 2. Guidelines for using the law within the Faculty of Law in the protection of global warming have not yet been enacted in force, but the green university policy, such as 5 Sor to the operation within the office and for students in voluntary part, with the assessment results at a high level (x = 3.53) to be the green Faculty of Law. 3. The preparation of the Faculty of Law announcement is specifically about reducing global warming, which is a measure of compulsory enforcement and should encourage alternative measures for the management of quality of green education, i.e. building knowledge about environmental conservation in every course.